A Language For Board Games - Krogh, Jennifer; Mattsson, Mattias; Pettersson, Emma; Sundqvist, Simon; Wiede, Carl; Åsberg, Mårten (My University, 2021)
This thesis covers the process and theory behind creating a domain-specific language for board games. This language is specifically made for positional board games and allows for further implementation of games in that category. A selection of example games were created and shipped with the language to showcase its usage. The language also has a graphical user interface allowing the user to easily play the games together with another player on the same computer. Possible future work regarding this project is suggested in the Discussion chapter, such as expanding the language to work with more game categories and the possibility to play online or against a computer.
Keywords: board games; positional games; connection games; domain-specific language